2021
DOI: 10.1177/26334895211039894
|View full text |Cite
|
Sign up to set email alerts
|

Screening for intimate partner violence in healthcare settings: An implementation-oriented systematic review

Abstract: Background Intimate partner violence (IPV) is a population health problem affecting millions of women worldwide. Screening for IPV within healthcare settings can identify women who experience IPV and inform counseling, referrals, and interventions to improve their health outcomes. Unfortunately, many screening programs used to detect IPV have only been tested in research contexts featuring externally funded study staff and resources. This systematic review therefore investigated the utility of IPV screening ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 117 publications
1
44
0
Order By: Relevance
“…This paper is the first study of its kind in Western Australia, and our findings and experience, along with those from other countries, 21 may encourage and guide other clinical services in implementing screening for IPV/RC.…”
Section: Discussionmentioning
confidence: 70%
“…This paper is the first study of its kind in Western Australia, and our findings and experience, along with those from other countries, 21 may encourage and guide other clinical services in implementing screening for IPV/RC.…”
Section: Discussionmentioning
confidence: 70%
“…Over the year of the evaluation, approximately 58,214 individuals visited the regional hospital ED with 60.8% and 63% being screened via questions 1 and 2, respectively. In comparison, Miller et al (2021) observed a median reach of IPV screening of 47% after conducting a systematic review, demonstrating the larger proportion of domestic abuse screens in this regional hospital ED relative to other EDs, if domestic abuse is even screened for. Though nurses or other health professionals have expressed discomfort in screening for domestic abuse (Garbin et al, 2015;Henriksen et al, 2017;Mauri et al, 2015), most patients expressed that they felt it was appropriate and important to screen for domestic abuse in the ED (Ben Natan et al, 2012).…”
Section: The Implementation Of Universal Screeningmentioning
confidence: 79%
“…Successfully implementing IPV screening programmes may help mitigate the harms resulting from IPV against women. IPV screening and response can identify women who experience IPV and form interventions to improve their health outcomes (Miller et al, 2021). Patients and providers agreed that one of the most critical factors for successful IPV screening is facilitating reporting of IPV.…”
Section: Discussionmentioning
confidence: 99%
“…An intimate relationship is an interpersonal relationship that involves physical or emotional intimacy, those in such a relationship may experience partner violence (GoPal et al, 2021). Intimate Partner Violence (IPV), is a severe public health problem, a human rights violation (Bandara et al, 2021), and an important barrier to equal participation, quality of life and personal, social and economic development (Weaver & Riebel, 2021); IPV affects millions of women globally (Miller et al, 2021).…”
Section: Introductionmentioning
confidence: 99%